2020
DOI: 10.1107/s1600577520010097
|View full text |Cite
|
Sign up to set email alerts
|

High accuracy determination of photoelectric cross sections, X-ray absorption fine structure and nanostructure analysis of zinc selenide using the X-ray extended range technique

Abstract: Measurements of mass attenuation coefficients and X-ray absorption fine structure (XAFS) of zinc selenide (ZnSe) are reported to accuracies typically better than 0.13%. The high accuracy of the results presented here is due to our successful implementation of the X-ray extended range technique, a relatively new methodology, which can be set up on most synchrotron X-ray beamlines. 561 attenuation coefficients were recorded in the energy range 6.8–15 keV with measurements concentrated at the zinc and selenium pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The widespread use of XRF and EDXRF argues strongly for increased understanding of these ratios and how to use and interpret them; the propagation errors and uncertainties of XANES and XAFS analysis, especially at low k, depend upon the stability and uniqueness of the definition of the edge and spline or other background subtraction; and more theoretical and experimental work is required in this area in attenuation, absorption and fluorescence measurements. Immediately, we can use this analysis to justify the data presented herein; and to emphasize or demonstrate the error of Singh Sidhu et al Previous work to obtain the edge jumps of the zinc K-edge using this method (Sier et al, 2020) on zinc selenide found the jump ratio to be r K, tot = 3.380. However, as this work was conducted on a compound, this value must be scaled by the relative atomic composition of zinc within zinc selenide (0.453) which converts the value to r K, tot = 7.461 as the attenuation ratio; and to r K = 3.406 as the photoabsorption ratio in the compound, and r K = 7.519 as the photoabsorption ratio for the Zn.…”
Section: X-ray Absorption Edge Jumps and Edge Jump Ratiosmentioning
confidence: 55%
See 1 more Smart Citation
“…The widespread use of XRF and EDXRF argues strongly for increased understanding of these ratios and how to use and interpret them; the propagation errors and uncertainties of XANES and XAFS analysis, especially at low k, depend upon the stability and uniqueness of the definition of the edge and spline or other background subtraction; and more theoretical and experimental work is required in this area in attenuation, absorption and fluorescence measurements. Immediately, we can use this analysis to justify the data presented herein; and to emphasize or demonstrate the error of Singh Sidhu et al Previous work to obtain the edge jumps of the zinc K-edge using this method (Sier et al, 2020) on zinc selenide found the jump ratio to be r K, tot = 3.380. However, as this work was conducted on a compound, this value must be scaled by the relative atomic composition of zinc within zinc selenide (0.453) which converts the value to r K, tot = 7.461 as the attenuation ratio; and to r K = 3.406 as the photoabsorption ratio in the compound, and r K = 7.519 as the photoabsorption ratio for the Zn.…”
Section: X-ray Absorption Edge Jumps and Edge Jump Ratiosmentioning
confidence: 55%
“…We, however, measure the zinc K-edge jump, jump ratio and jump factor from the current data herein and hence use an alternative XERT-like method. Synchrotron X-rays are allowed to pass through the sample to measure attenuation coefficients, from which photoabsorption coefficients and edge-jump ratios can be derived (Chantler et al, 2001;Rae et al, 2010;Sier et al, 2020). Following Fig.…”
Section: X-ray Absorption Edge Jumps and Edge Jump Ratiosmentioning
confidence: 99%
“…A = 1/[t] from the thickness determination, f is the fluorescence counts and , are constants to be fitted. and define the fraction of fluorescence which enters the upstream and downstream (fluorescence) detectors (Sier et al, 2020;Trevorah et al, 2019;Islam et al, 2015). Upon inspection, any scattering is below the noise level in the upstream ion chamber -hence is set to zero, with particularly fitted from the high-energy E or high k-range.…”
Section: Derivative Peakmentioning
confidence: 99%
“…Hence it is particularly important if there are any energy-dependent functionalities above the edge. Previous work with zinc at the same beamline measured the scattering and fluorescence contributions in each ion chamber (Sier et al, 2020;Trevorah et al, 2019;Islam et al, 2015). Hence we require a functional to match the scattering correction of each data set.…”
Section: Appendix C Thickness Determinationmentioning
confidence: 99%
See 1 more Smart Citation